Engineering copper and copper-based materials for a post-antibiotic era - Wang, Yingxian; Wen, Tongqiang; Mao, Fuchao; Yang, Shaozhe; Zhang, Qingwei; Fu, Xiuhong; Zhai, Chongkai; Zhang, Hewei (Frontiers in Bioengineering and Biotechnology, 2025)
In recent years, the emergence of multidrug-resistant bacteria and the frequent outbreaks of novel viral pathogens have intensified the demand for novel, efficient, and low-toxicity antimicrobial materials. Copper and copper-based materials, owing to their broad-spectrum and potent antimicrobial properties, have attracted increasing attention across diverse fields, including medicine, agriculture, and environmental science. This review provides a comprehensive overview of the development history, antimicrobial and antiviral mechanisms, fabrication techniques, and bioactive characteristics of copper and its derivatives. It further highlights their current applications in healthcare, public infrastructure, food processing, textiles, and modern agriculture. Challenges associated with material stability, cytotoxicity and environmental safety, are critically discussed. Finally, future perspectives are proposed, emphasizing advances in material synthesis, the development of stable nano-coatings, controlled release strategies, low-toxicity and low-resistance formulations, establishment of standardized pharmacological and toxicological evaluation systems, drug delivery applications, and copper pollution control. This review aims to inform future efforts in overcoming the current limitations of copper-based antimicrobials and supporting their potential future integration into applications across medicine, public health, environmental protection, and agricultural innovation, contingent upon resolving current translational and regulatory challenges.